A Conceptual Model: The Impact of Sociodemographic on Coronary Heart Disease - Md Kassim, Aza Azlina; Mohamed, Juliza; Zainal Azim , Zainal Azhar; Hafiz Rosli , Mohamad; Abd Rahim , Mohd Azrin; Salleh, Mohd Nazil (International Journal of Scientific Research and Management (IJSRM), 2020)
The paper aims to examine the conceptual model on the impact of sociodemographic towards coronary heart disease. There is still limited study on the association between cost of living particularly the cost of food and housing and its impact on coronary heart disease. Therefore, this study incorporates five essential sociodemographic attributes namely, cost of food, children education cost, housing cost, smoking habit and gender. The study provides greater understanding on how the cost of living and lifestyle may give impact to coronary heart disease. It may provide the awareness among the regulators as the society faces burden of high cost of living. The burden may threaten the Malaysians quality of life particularly the lower income group.